Threats to public figures and association with approach, as a proxy for violence: The importance of grievance - James, David V.; Farnham, Frank R.; Allen, Philip; Martinsone, Ance; Sneader, Charlie; Wolfe Murray, Andrew (Frontiers in Psychology, 2022)
The adoption of the term grievance-fuelled violence reflects the fact that similarities exist between those committing violent acts in the context of grievance in different contexts, so potentially allowing the application of insights gained in the study of one group to be applied to others. Given the low base-rate of violence, studies in the field of violence against those in the public eye have tended to use, as a proxy for violence, attempts by the individuals concerned to achieve unwarranted and unwanted proximity to the subject of their attention, given that approach is a necessary prerequisite for most forms of attack. In such studies, one factor that has frequently been considered is whether the making of threats is associated with subsequent approach. Results have been varied, with no correlation found in some, a negative correlation in others, and a positive correlation in at least one. Such studies have been retrospective, using case files prepared for other purposes, and samples of cases have been selected according to their victims’ sector of employment – for instance, politicians, celebrities, judiciary, and the corporate world. The current study of a sample of 126 threat assessment cases, using a mixed prospective and retrospective methodology, looks at the associations between the making of threats and subsequent approach from a different angle – that of a standardised and validated classification of underlying motivation. It finds that particular types and forms of threat are significantly associated with subsequent approach in cases that are fuelled by grievance, but not in those with the motivation of seeking a relationship. Further, when a sample with a mixture of motivational categories was examined in the manner of previous studies, such associations with threat were not apparent. These results refine the existing understanding of the significance of threats in public-facing cases. Future research projects in this area might usefully incorporate consideration of underlying motivation, in particular grievance.